“Porque não é o escrever em si, é ver como é que está escrito”: discursos sobre letramentos acadêmicos em inglês em uma comunidade de prática de química - Lee, Amy Graham (2019)
Although there is a long history of research in the area of Academic Literacies in Brazil, Ferreira e Stella (2018, p. 17) affirm that studies on learning and teaching writing for academic purposes in Brazilian universities is still a neglected action. Considering the increased exigence to publish internationally and the need to ground pedagogical practices for writing in results from research in each of the different disciplinary contexts (MOTTA-ROTH, 2013, p. 12), this study aims to explore academic literacy practices in English and their development in a highly-ranked graduate program that presents high productivity in international publications in English, the Graduate Program in Chemistry at UFSM. Toward that end, we propose the following research questions: 1) which academic literacy practices are most valued by the professors, both in terms of their own practices and those of their students, and why? 2) how did the professors develop their own academic literacies and which aspects present the greatest level of difficulty for them? 3) what dynamics of coauthorship and/or pedagogic approaches do the professors adopt and which aspects of writing present the greatest level of difficulty for their students? The interdisciplinary theoretical framework combines Genre Studies (BAZERMAN, 2007; BAWARSHI; REIFF, 2013), Academic Literacies (LEA; STREET 1998, IVANIC 1998) and Critical Discourse Analysis (FAIRCLOUGH, 2003), as well as the concepts of Communities of Practice and Legitimate Peripheral Participation (LPP) (LAVE; WENGER, 1991; WENGER, 1998). Using data generated from a semistructured questionnaire and qualitative interviews, we analyzed the discourses of the professors, exploring whether the development of skills, competencies and discursive conditions involved in academic literacies in English is mediated by LPP in a community structured to provide increasing access to new members and capacitate them to participate fully in the community. We argue that the community studied demonstrates variable degrees of student LPP. Professors who report a greater degree of LPP along with a network for collaborating on writing and revising among the students also report less difficulty in the development of the students’ academic literacies. On the other hand, even when a greater degree of LPP is observed, we detect the need for pedagogical approaches that could supplement the existing LPP. The professors’ discourse reveals a dialectical tension, where, on the one hand, scientific writing is portrayed as easy and, on the other hand, writing articles is characterized as difficult and the professors report that students encounter great difficulty. We argue that this tension is related, in most of the accounts, to a pedagogical approach in line with the notion of academic literacies as cognitive skills acquired through tacit knowledge, rather than through explicit teaching within a perspective of academic literacies as social practices. In this sense, we recommend the creation of collaborative networks in the community and the introduction of a collaborative and transformative pedagogical approach that will allow students to identify as authors within the community, viewing academic literacies as social actions and developing a critical eye toward the texts and genre systems that constitute them.